Differential Ecological Specificity of Protist and Bacterial Microbiomes across a Set of Termite Species - Waidele, Lena; Korb, Judith; Voolstra, Christian R.; Künzel, Sven; Dedeine, Franck; Staubach, Fabian (Frontiers in Microbiology, 2017)
The gut microbiome of lower termites comprises protists and bacteria that help these insects to digest cellulose and to thrive on wood. The composition of the termite gut microbiome correlates with phylogenetic distance of the animal host and host ecology (diet) in termites collected from their natural environment. However, carryover of transient microbes from host collection sites are a concern and might contribute to the ecological imprints on the termite gut microbiome. Here, we set out to test whether an ecological imprint on the termite gut microbiome remains, when focusing on the persistent microbiome. Therefore, we kept termites under strictly controlled dietary conditions and subsequently profiled their protist and bacterial gut microbial communities using 18S and 16S rRNA gene amplicon sequencing. . The species differ in their ecology; while three of the investigated species are wood-dwellers that feed on the piece of wood they live in and never leave except for the mating flight, the other two species regularly leave their nests to forage food. Despite these prominent ecological differences, protist microbiome structure aligned with phylogenetic relatedness of termite host species. Conversely, bacterial communities seemed more flexible, suggesting that microbiome structure aligned more strongly with the foraging and wood-dwelling ecologies. Interestingly, protist and bacterial community alpha-diversity correlated, suggesting either putative interactions between protists and bacteria, or that both types of microbes in the termite gut follow shared structuring principles. Taken together, our results add to the notion that bacterial communities are more variable over evolutionary time than protist communities and might react more flexibly to changes in host ecology.